2013
DOI: 10.1039/c3dt50341k
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of Au-loaded Fe3O4@C composite microspheres with superior SERS detection and catalytic degradation abilities for organic dyes

Abstract: Bifunctional Au-loaded Fe3O4@C composite microspheres were controllably synthesized by coating of Au nanoparticles (NPs) on the surface of the poly(diallyldimethylammonium chloride) (PDDA) functionalized Fe3O4@C microspheres. The amount of Au loading can be effectively tuned by altering the feeding amounts of solution Au NPs or further growth. The obtained Au-loaded Fe3O4@C composite microspheres exhibit both superior surface-enhanced Raman scattering (SERS) sensitivity and catalytic degradation activity for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(38 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…Zhang et al successfully synthesized Fe 3 O 4 \SiO 2 \Ag composite and investigated its potential application as an antibacterial material in water disinfection (Zhang et al 2011). Gan et al had developed Fe 3 O 4 @C@Au composite microspheres with superior SERS detection and recyclable catalytic degradation abilities for organic dyes (Gan et al 2013). Therefore, the synthesis of multifarious magnetic nanocomposites with multiple properties arouses more and more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al successfully synthesized Fe 3 O 4 \SiO 2 \Ag composite and investigated its potential application as an antibacterial material in water disinfection (Zhang et al 2011). Gan et al had developed Fe 3 O 4 @C@Au composite microspheres with superior SERS detection and recyclable catalytic degradation abilities for organic dyes (Gan et al 2013). Therefore, the synthesis of multifarious magnetic nanocomposites with multiple properties arouses more and more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the polyelectrolyte PDDA that acts as a linker in the assembly of Ag@C SHINs can minimize the background of the SERS spectra, [41][42][43] owing to its small Raman crosssection. Briefl y, negatively charged Fe 3 O 4 @C and Ag@C SHINs were synthesized separately using one-pot solvothermal methods.…”
Section: Resultsmentioning
confidence: 99%
“…S4, Supporting information). In the context of this work, it was found as particularly useful because it is well‐known to adsorb strongly to textiles such as cotton, wool and silk and on the other side several Raman studies have reported a strong SERS signal when it is used as the analyte …”
Section: Surface Enhanced Raman Scattering Studies Using Ag/linen Nanmentioning
confidence: 99%